Hydrodynamical models of type II plateau supernovae - Bersten, Melina Cecilia (2011)
We present bolometric light curves of Type II plateau supernovae obtained using a newly developed, one-dimensional Lagrangian hydrodynamic code with flux-limited radiation diffusion. Using our code we calculate the bolometric light curve and photospheric velocities of SN 1999em, obtaining a remarkably good agreement with observations despite the simplifications used in our calculation. The physical parameters used in our calculation are E = 1.25foe, M = 19 M ⊙, R = 800 R ⊙, and M Ni = 0.056 M ⊙. We find that an extensive mixing of 56Ni is needed in order to reproduce a plateau as flat as that shown by the observations. We also study the possibility to fit the observations with lower values of the initial mass consistently with upper limits that have been inferred from pre-supernova imaging of SN 1999em in connection with stellar evolution models. We cannot find a set of physical parameters that reproduce well the observations for models with pre-supernova mass of ≤12 M ⊙, although models with 14 M ⊙ cannot be fully discarded.